5th International Symposium on Fluid Structure Interaction, Aeroelasticity, and Flow Induced Vibration and Noise 2002
DOI: 10.1115/imece2002-33405
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Acoustic Energy Absorbers to Suppress Acoustic Resonance in Tube Bundles of Boiler Plants

Abstract: The present paper deals with acoustic resonance in tube bundles which occurred in actual boiler plants. A practical method to suppress the resonant noise is proposed based on scale model tests. In those experiments, besides the transverse modes which are relatively well-known, longitudinal modes which are known to be difficult to suppress, were realized. The relation of both kinds of acoustic modes to vortex shedding frequency was clarified. In the following step, a design method of the acoustic energy absorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The triangular structure under the test apparatus is the model of the recovery system of the combustion ash. The similarity of this device in detail was explained in the paper [14].…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The triangular structure under the test apparatus is the model of the recovery system of the combustion ash. The similarity of this device in detail was explained in the paper [14].…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
“…The acoustic resonance generated from this test model could be suppressed by setting the acoustic absorbers [14]. Acoustic absorbers were made of glass wool and they were covered by acrylic plates.…”
Section: Vortex Shedding Characteristics Without Acoustic Resonancementioning
confidence: 99%
“…2.48 [166] suffered a resonance in the transverse and longitudinal modes. A scale model experiment discovered these modes.…”
Section: Coal-fired Boilermentioning
confidence: 99%
“…They identified the resonant mode shapes and showed that the resonance frequencies of longitudinal modes are almost double those of transverse modes. On the other hand, Nishida et al [166] used plant boiler scale models. Their results on resonance phenomena are shown in Figs.…”
Section: Review Of Research On Longitudinal Mode Resonancementioning
confidence: 99%
See 1 more Smart Citation